FORMULASI DAN EVALUASI KRIM EKSTRAK DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) DENGAN VARIASI KONSENTRASI ASAM STEARAT DAN TRIETANOLAMIN - Laela Nurfitri; Nur Cholis Endriyatno (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
The fragrant pandan leaf (Pandanus amaryllifolius Roxb.) contains flavonoid compounds that can function as a sunscreen. Sunscreen preparations are generally in the form of creams. In cream formulations, emulsifiers play a crucial role in imparting physical properties to the cream. The objective of this research is to determine the influence of the combination of stearic acid and triethanolamine on the physical properties and stability of the cream and to identify the optimal emulsifier concentration. Cream formulations were prepared in three formulations with a combination of stearic acid and triethanolamine (TEA), namely F I (17%: 3.5%), F II (18%: 3%), and F III (19%: 2.5%). The cream formulations underwent physical evaluations such as organoleptic testing, homogeneity testing, viscosity testing, adhesion testing, pH testing, skin irritation testing, spreading power testing, and stability testing. The data obtained were analyzed using One Way ANOVA (analysis of variance) with a confidence level of 95%. The research data results showed that the addition of stearic acid and trietanolamin affected the viscosity, pH value, spreading power, and adhesion of the cream but did not affect the organoleptic properties, stability, homogeneity, and skin irritation. Based on the physical properties and statistical tests, the concentration of stearic acid and trietanolamin emulsifier (17%: 3.5%) was found to be the best.